Soil properties under different land uses and slope gradients: Implications for sustainable land management in the Tach Karnuary watershed, Northwestern Ethiopia - Ewunetu, Tenagne; Selassie, Yihenew G.; Molla, Eyayu; Admase, Habtamu; Gezahegn, Ashenafei (Frontiers in Environmental Science, 2025)
Introduction:Soil degradation resulting from land use changes and topographic variations poses a significant threat to agricultural productivity and environmental sustainability in the Northwestern Ethiopian Highlands. Assessing the influence of land use and slope gradient on soil physicochemical properties is crucial for developing sustainable land management strategies.Methods:This study investigated the effects of four land-use types (cultivated land, grazing land, forest land, and eucalyptus plantations) and two slope gradients (upper and lower slopes) on selected soil properties in the Tach Karnuary watershed in Northwestern Ethiopia. Twenty-four composite soil samples were collected from 0 to 20 cm soil depth in triplicate across all land use and slope categories. In addition, undisturbed soil samples were obtained using a core sampler to assess the bulk density. Standard laboratory procedures were employed to analyze the physical properties (bulk density, porosity, and texture) and chemical properties (pH, organic matter, total nitrogen, available phosphorus, cation exchange capacity, and exchangeable cations). Data were statistically analyzed using analysis of variance (ANOVA).Results:The ANOVA results revealed that land-use type significantly (p < 0.05) affected most soil physicochemical properties, including texture, bulk density, porosity, pH, available phosphorus, organic matter, total nitrogen, cation exchange capacity, and exchangeable cations. Likewise, the slope gradient had a highly significant (p < 0.01) effect on the bulk density, porosity, pH, organic matter, available phosphorus, total nitrogen, cation exchange capacity, and exchangeable cations.Discussion:Soils on upper slopes exhibited lower fertility and more degraded physical conditions than those on lower slopes, primarily because of erosion and nutrient loss. variations in soil properties were also observed across the different land-use types. These findings underscore the urgent need for slope and land use-specific management interventions to mitigate soil degradation, enhance soil fertility, and promote sustainable land use in the erosion-prone landscapes of the Northwestern Ethiopian Highlands.